Dialektika Politik Islam Di Indonesia - Juhrana Susilo; Zasmita Auliah Wardani; Kurniati (AL-Ikhtiar : Jurnal Studi Islam, 2026)
The dialectic of Islamic politics in Indonesia is a phenomenon that demonstrates the dynamic relationship between Islamic values, political power, and national realities in a pluralistic society. This study aims to analyze the development of the dialectic of Islamic politics in Indonesia, the factors influencing it, and its implications for democracy and national life. This study employed library research with a qualitative-descriptive approach. Data were obtained from various sources, such as books, scientific journals, academic articles, official documents, and previous research relevant to the study's theme. Data analysis was conducted using content analysis techniques by reviewing, classifying, interpreting, and summarizing various pieces of information related to the development of Islamic politics in Indonesia. The results show that the dialectic of Islamic politics in Indonesia has been ongoing since the colonial period, the struggle for independence, the era of parliamentary democracy, the Old Order, the New Order, and the Reformation era. This dynamic is characterized by processes of interaction, negotiation, compromise, and contestation between the political aspirations of Muslims and the national political system. Islamic politics in Indonesia has developed in various forms, including through political parties, community organizations, social movements, and community participation in the public sphere. Research findings also indicate that Islamic politics in Indonesia tends to move toward moderation, prioritizing the values ​​of democracy, tolerance, and nationalism without abandoning Islamic principles. On the other hand, the development of information technology and the strengthening of identity politics pose new challenges that influence the interaction between religion and politics in society. Abstrak Dialektika politik Islam di Indonesia merupakan fenomena yang menunjukkan hubungan dinamis antara nilai-nilai keislaman, kekuasaan politik, dan realitas kebangsaan dalam masyarakat yang plural. Penelitian ini bertujuan untuk menganalisis perkembangan dialektika politik Islam di Indonesia, faktor-faktor yang memengaruhinya, serta implikasinya terhadap kehidupan demokrasi dan kebangsaan. Penelitian ini menggunakan metode library research dengan pendekatan kualitatif-deskriptif. Data diperoleh dari berbagai sumber pustaka, seperti buku, jurnal ilmiah, artikel akademik, dokumen resmi, dan hasil penelitian terdahulu yang relevan dengan tema kajian. Analisis data dilakukan melalui teknik content analysis dengan menelaah, mengklasifikasikan, menginterpretasikan, dan menyimpulkan berbagai informasi yang berkaitan dengan perkembangan politik Islam di Indonesia. Hasil penelitian menunjukkan bahwa dialektika politik Islam di Indonesia telah berlangsung sejak masa kolonial, masa perjuangan kemerdekaan, era demokrasi parlementer, Orde Lama, Orde Baru, hingga era Reformasi. Dinamika tersebut ditandai oleh proses interaksi, negosiasi, kompromi, dan kontestasi antara aspirasi politik umat Islam dengan sistem politik nasional. Politik Islam di Indonesia berkembang dalam berbagai bentuk, baik melalui partai politik, organisasi kemasyarakatan, gerakan sosial, maupun partisipasi masyarakat dalam ruang publik. Temuan penelitian juga menunjukkan bahwa politik Islam di Indonesia cenderung bergerak ke arah moderasi dengan mengedepankan nilai-nilai demokrasi, toleransi, dan kebangsaan tanpa meninggalkan prinsip-prinsip ajaran Islam. Di sisi lain, perkembangan teknologi informasi dan menguatnya politik identitas menjadi tantangan baru yang memengaruhi pola interaksi antara agama dan politik dalam kehidupan masyarakat.